Hydroxyl radical scavenging factor measurement using a fluorescence excitation-emission matrix and parallel factor analysis in ultraviolet advanced oxidation processes. (November 2020) - Hwang, Tae-Mun; Nam, Sook-Hyun; Lee, Juwon; Koo, Jae-Wuk; Kim, Eunju; Kwon, Minhwan
Abstract: The performance of the UV/H2 O2 advanced oxidation process (AOP) is dependent on water quality parameters, including the UV absorbance coefficient at 254 nm and hydroxyl radical (OH) water background demand (scavenging factor, s −1 ). The OH scavenging factor represents the OH scavenging rate of the background substances in the water matrix, and it is known to be one of the key parameters to predict the performance of the UV/H2 O2 process. The OH scavenging factor has been determined experimentally by using a probe compound such as p CBA and rhodamine B. The experimental method has been validated to accurately predict the micropollutants removal in the UV/H2 O2 process, but there is a need for an easier and simple method of determining the OH scavenging factor. We evaluated the alternative method to analyze the OH scavenging factor using fluorescence excitation-emission matrix and parallel factor analysis (F-EEM/PARAFAC). The correlation between OH scavenging factor and the spectroscopic characteristics and structure of different organic matter types was evaluated. Organic matter was characterized using a fluorescence excitation-emission matrix, parallel factor analysis, and liquid chromatography-organic carbon detection. Second-order reaction rates of humic acid sodium salt, sodium alginate, Suwannee River humic acid and bovine serum albumin were calculated as 1.30 × 10 8 M −1 s −1, 1.39 × 10 8 M −1 s −1, 1.03 × 10 8 M −1 s −1, and 3.17 × 10 7 M −1 s −1, respectively. Results of PARAFAC analysis, the ratio of humic and fulvic fluorescence component 2 to terrestrial humic-like fluorescence component 1 (C2/C1), and OH scavenging factor showed high linearity. A predictive model, which combines with the F-EEM/PARAFAC method, predicted the optimal UV and H2 O2 dose to achieve target compound removal. Highlights: To predict the removal rate of the target compound in the AOP process, OH must be interpreted quantitatively. The reaction rates for the OH reaction with DOM were experimentally determined. The kinetic model combined with OH scavengers monitoring method allows the optimal UV and H2 O2 dose. Fluorescence spectroscopy, which can provide powerful simply techniques to predict OH radical scavengers by characterizing organic matters.